ACCELERATED UNIVERSE FROM G-ESSENCE - Belisarova, F.B.; Yerzhanov, K.K.; Tsyba, P.Yu.; Myrzakul, Sh.R.; Kulnazarov, I.I. (Recent Contributions to Physics, 2017)
In the present work we analyze the g-essence model for the particular Lagrangian: L=R+2[aXn+eY-V(y/,y)]. The g-essence models were proposed recently as an alternative and as a generalization to the scalar k-essence. We have presented the 3 types solutions of the g-essence model. We reconstructed the corresponding potentials and the dynamics of the scalar and fermionic fields according the evolution of the scale factor. The obtained results show that the g-essence model can describes the decelerated and accelerated expansion phases of the universe.